Work–life balance and gig work: 'Where are we now' and 'where to next' with the work–life balance agenda?. (September 2021) - Warren, Tracey
The article asks 'where are we' in the study of work–life balance within Industrial Relations and 'where to next' if we are to identify levers for positive change in workplace gender equality as technology brings the potential for smoothing or disrupting how women and men from different class groups work and care. It first shines a classed lens on the mainstream work–life balance agenda to pinpoint limitations in its heavy focus on the time squeezes reported by financially secure middle-class workers and its neglect of money matters. Then, via an enhanced conceptualisation, the article considers the ramifications of the growth in gig work for work–life balance. Gig work is promoted as offering flexibility and autonomy, enabling carers to work and care, but it is performed without the safety nets that are more common in formal employment. It can bring unpredictability in both work-time and income, work intensification and financial hardship that all impact work–life balance. 'Where to next' is developing a more inclusive approach that recognises gender, class and other types of diversity in order to lever workplace gender equality for all.